IMPLEMENTASI METODE SPIRAL DALAM PEMBUATAN PERANGKAT PEMBELAJARAN BERBASIS WEB UNTUK PENGAJARAN EFEKTIF - Wirhan Fahrozi; Erwin Ginting Erwin Ginting; Deni Adhar; Nidia Enjelita Saragih (Politeknik Bisnis Indonesia, 2024)
This research aims to develop a web-based learning tool using the spiral diagram method, which is designed to increase the effectiveness of the teaching and learning process at Musabbihin Middle School. The background to this research notes that many previous studies only focused on theory without producing applications that could be used in real life. This research adopts data collection methods through field studies and literature studies, and uses a spiral diagram approach which includes the stages of communication, planning, modeling, construction and deployment. The research results show that the resulting application has three types of users, namely teachers, school principals and supervisors, with each having a clear role in managing and evaluating learning tools. These applications enable flexible and independent access to learning materials, assist in time management, and facilitate performance evaluation, ultimately increasing student independence and learning effectiveness.